Some Issues of the Application of Criminal Responsibility Rules for the Schedule of the Worker of the Contract Service, the Contract Manager, the Member of the Purchasing Commission - E. I. Chekmezova (Сибирское юридическое обозрение, 2018)
The legislation on the contract system in the field of procurement for state and municipal needs is a complex legal mechanism, the functioning of which complicates the corruption component. Parties to a state (municipal) contract must clearly recognize the full range of responsibility for breaking the law. The application to the participants of the procurement process of the norms of the Criminal Code is a last resort by the state. The legislator, using a differentiated approach, established responsibility for the contract service worker, the contract manager, a member of the procurement commission, and persons who are interested in bribing them. When creating a norm, the rules of legal engineering were not observed, the experience of building norms provided by Art. 204, 2041, 2042, 290, 291, 2911, 2912 of the Criminal Code of the Russian Federation, provisions of the theory of criminal law on corpus delicti and on the institution of exemption from criminal liability.